Current Advance of Immune Evasion Mechanisms and Emerging Immunotherapies in Renal Cell Carcinoma - Jian, Yuli; Yang, Kangkang; Sun, Xiaoxin; Zhao, Jun; Huang, Kai; Aldanakh, Abdullah; Xu, Zhongyang; Wu, Haotian; Xu, Qiwei; Zhang, Lin; Xu, Chunyan; Yang, Deyong; et al. (Frontiers in Immunology, 2021)
Renal cell carcinoma is a highly heterogeneous cancer group, and the complex microenvironment of the tumor provides appropriate immune evasion opportunities. The molecular mechanism of immune escape in renal cell carcinoma is currently a hot issue, focusing primarily on the major complex of histocompatibility, immunosuppressive cells, their secreted immunosuppressive cytokines, and apoptosis molecule signal transduction. Immunotherapy is the best treatment option for patients with metastatic or advanced renal cell carcinoma and combination immunotherapy based on a variety of principles has shown promising prospects. Comprehensive and in-depth knowledge of the molecular mechanism of immune escape in renal cell carcinoma is of vital importance for the clinical implementation of effective therapies. The goal of this review is to address research into the mechanisms of immune escape in renal cell carcinoma and the use of the latest immunotherapy. In addition, we are all looking forward to the latest frontiers of experimental combination immunotherapy.